EFEK JUS BUAH BELIMBING (AVERRHOA CARAMBOLA L.) TERHADAP KADAR GLUKOSA DARAH TIKUS PUTIH (RATTUS NORVEGICUS) JANTAN GALUR WISTAR YANG DIBEBANI GLUKOSA - ., Adam Ridha (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background : Diabetes is a primary condition of hyperglycemia that canincrease the risk of microvascular damage (retinopathy, nephropathy, andneuropathy). Star fruit (carambola L. Averrhoa) (100mg), empirically usedto lower blood glucose levels in patients with diabetes mellitus. Objective :To determine the effect of star fruit juice on blood glucose levels of wistarstrain white male (Rattus norvegicus) rats with glucose pre-load. Method :This was an experimental study with controlled time series design andusing oral glucose tolerance test. The method used in determining bloodglucose level is using glucometer easy touch. This Study was using 25white male wistar rats weighing 150-250 grams, and 1.5-3 months oldwhich divided randomly into 5 groups: negative control group (aquades),positive control group (Metformin 45mg / kgBW), starfruit juice group withdose I (6.3 mg / kgBW), dose II (12.6 mg / kgBW), and dose III (25.2 mg /kgBW). Result : This study shows that there are significant differencesbetween dose I group (6.3 mg / kgBW), dose II group (12.6 mg / kgBW),and dose III group (25.2 mg / kgBW) to the negative control group(p<0,001) and the positive control group. Conclusion : Star fruit juicedose I (6.3 mg / kgBW), dose II (12.6 mg / kgBW), and dose III (25.2 mg /kgBW) effective (p <0.05) in lowering blood glucose levels of white malewistar rats with glucose pre-load.